Deep Subwavelength Power Concentration-Based Hyperbolic Metamaterials. (26th September 2012) - Kaur, Amanpreet; Banerjee, Saptarshi; Zhao, Wangshi; Venkataraman, Jayanti; Lu, Zhaolin
Abstract : Hyperbolic metamaterials can manipulate electromagnetic waves by converting evanescent waves into propagating waves and thus support light propagation without diffraction limit. In this paper, deep subwavelength focusing (or power concentration) is demonstrated both numerically and experimentally using hyperbolic metamaterials. The results verify that hyperbolic metamaterials can focus a broad collimated beam to spot size of ~ λ 0 /6 using wired medium design for both normal and oblique incidence. The nonmagnetic design, no-cut-off operation, and preferred direction of propagation in these materials significantly reduce the attenuation in electromagnetic waves.